An analysis of students’ difficulties in comprehending narrative text - Desi Sapitri; Fitri Novia; Rachmanita (Relawan Jurnal Indonesia, 2020)
The objective of this study was to find out students’ difficulties faced by the Eight Grade Students at SMP N3 Tanjung Raja in Comprehending English reading text. The method was used descriptive qualitative research. The participants of this study was all of the eighth grade students of SMP Negeri 3 Tanjung Raja. The technique for collecting the data was multiple choice. Based on the result, it was found that the percentage of difficulty in indicator not clearly stated information was 55.90%, the percentage of difficulty in indicator reference of the text was 59.54%, the percentage of difficulty in indicator find moral value of the text was 64.23%, the percentage of difficulty in indicator find the deducing meaning was 55.27%, the percentage of difficulty in indicator find the specific information was 56.35%, the percentage of difficulty in indicator find the detailed information was 67.05%, and the percentage of difficulty in indicator find the main idea was 54.81%